Digital library technology in J‐ISIS: concept, implementation and comparison with GSDL. Issue 1 (2014) - ,
Abstract : Purpose – Although the new J‐ISIS software from UNESCO, based on Berkeley DB and Lucene technology, complies with some of the technical requirements as seen necessary for digital library applications, an easy way of building collections so far was not available. The purpose of this paper is to give a report on some necessary DL technological requirements, such as the capability to deal with any metadata structure and alphabets and full‐text indexing of documents of any length, and how J‐ISIS can deal with these, as well as on the production of the DL interface for digital library applications based on Tika technology.Design/methodology/approach – A brief comparison is made with a well‐established DL software, i.e. Greenstone Digital Library, regarding the concepts and performance.Findings – While using a quite different architecture and approach, the test shows that J‐ISIS can process the documents faster and with more economical storage efficiency, inviting UNESCO to invest more into it in order to allow incorporation of some more advanced features like Greenstone's capability to process intra‐document segments and images, but also to allow for new exciting features for digital libraries such as interactivity.Research limitations/implications – The research is based on the J‐ISIS prototype implementation of digital library technology and could only be tested on a limited set of documents.Practical implications – Librarians interested in building digital library collections, esp. when doing this integrated with their library systems and catalogs, have a viable new option now within the FOSS‐market.Originality/value – This is the first description on J‐ISIS for digital libraries. Acknowledgements : With full credits being due to Jean‐Claude Dauphin for his invaluable help with the J‐ISIS coding challenges. This article is based on the MA thesis "Extension with digital library technology of UNESCO's J‐ISIS database software" submitted by H.H. Berhe, January 2012, VUB Brussels, Faculty of Engineering under the supervision of the author.